A framework based on Twitter and big data analytics to enhance sustainability performance. Issue 1 (15th October 2018) - Queiroz, Maciel M.
Abstract: This study presents two environmental frameworks based on Twitter and the big data analytics approach. This research aims to provide novel frameworks for the use of environmental decision makers, practitioners, and scholars to enhance environmental management and sustainability performance. An example of framework utilization is supplied with a case study of the hashtag #CleanerProduction.